(untitled) (Politeja, 2022)
RECKONING WITH THE PAST? ON THE ILLUSORY DE-FASCISATION OF ITALY IN THE PERIOD OF TRANSFORMATION (1943-1948) This chapter discusses de-fascisation process in Italy during the systemic transformation in 1943-1948. It will examine whether the national reconciliation policy pursued by the Alcide De Gasperi’s governments in the second half of the 1940s contributed to the emergence of a societal vision of Mussolini’s relatively mild dictatorship, which in turn made full reckoning with the fascist legacy impossible. More specifically, the chapter discusses the following issues: 1) illusory de-fascisation of Italy’s administrative apparatus, 2) the Togliatti amnesty and the absence of Italian Nuremberg, 3) anti-fascist milieu narratives on fascism as a closed chapter in national history, and 4) the phenomenon of the renaissance of neo-fascist groups against the background explicit legal norms prohibiting practicing any form of apology for the Mussolini.